1983
DOI: 10.1085/jgp.81.5.643
|View full text |Cite
|
Sign up to set email alerts
|

Calcium reduces the sodium permeability of luminal membrane vesicles from toad bladder. Studies using a fast-reaction apparatus.

Abstract: Regulation of the sodium permeability of the luminal membrane is the major mechanism by which the net rate of sodium transport across tight epithelia is varied. Previous evidence has suggested that the permeability of the luminal membrane might be regulated by changes in intracellular sodium or calcium acti¥ities. To test this directly, we isolated a fraction of the plasma membrane from the toad urinary bladder, which contains a fast, amiloridesensitive sodium flux with characteristics similar to those of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2

Year Published

1983
1983
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 49 publications
1
24
2
Order By: Relevance
“…In agreement with a previous report (Chase & A1-Awqati, 1983) we found that including submicromolar concentrations of free Ca 2+ in the vesicles, substantially lowers the channel-mediated flux. These results appear, however, to be different from those obtained recently using rat collecting tubules (Palmer & Frindt, 1986).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with a previous report (Chase & A1-Awqati, 1983) we found that including submicromolar concentrations of free Ca 2+ in the vesicles, substantially lowers the channel-mediated flux. These results appear, however, to be different from those obtained recently using rat collecting tubules (Palmer & Frindt, 1986).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we attempted to manipulate the intracellular Ca2+ concentration in a different way, by removal of Na+ from the serosal solution. Recently, the presence of a Na+/Ca2+ exchange mechanism at the basolateral membrane offrog skin (Grinstein & Erlij, 1978) and toad bladder (Chase & Al-Awqati, 1983) has been demonstrated. This transport system is responsible for the extrusion of Ca2+ from the cytosolic compartment and operates through the inward-oriented driving force for Na+.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has been presented for the presence of a Na-Ca countertransport mechanism at the basolateral membranes of toad (Chase & A1-Awqati, 1983 ;Arruda et al, 1982) and turtle urinary bladder (Arruda, Sabatini & Westenfelder, 1982), rat small intestine (Hildmann, Schmidt & Murer, 1982), Necturus renal proximal tubule (Lee, Taylor & Windhager, 1980), and frog skin (Grinstein & Erlij, 1978) whereby the movement of Na into the cell across the basolateral membrane energizes the uphill extrusion of Ca from the cell across that barrier. If, as in other tissues (Blaustein, 1974), this mechanism is rheogenic involving the counterflow of more than 2 Na per Ca, the driving force for Ca extrusion is derived from both the Nachemical gradient and the electrical potential difference across that membrane.…”
Section: Sodium Entry Across the Apical Membranementioning
confidence: 99%